Perancangan Wisata Kuliner Pada Taman Sri Deli Kota Medan - Rizky Khairi; Faurantia Forlana Sigit; Novalinda; Rahmadhani Fitri (Universitas Medan Area, 2023)
The condition of Taman Sri Deli currently functions as a public space where one of its functions is used as a culinary tourism spot. The problem that occurs is when the Ramadan Fair event is held and there are road closures that disrupt the activities of road users. Therefore, it is necessary to do a solution by referring to the design of the culinary tourism area allocated in Taman Sri Deli in order to maximize the design that can support the activities of existing events. The theme that will be applied in the design of Taman Sri Deli Culinary Tour is the Green Space theme.